Oral comprehension and production in English through the communicative approach. (Revista Investigación & praxis en CS Sociales, 2022)
This paper aimed to analyze the incidence of the use of the communicative approach on the production and oral comprehension of English as a foreign language in sixth grade students using a qualitative approach and action research as research design for students to analyze the impact and effectiveness of the selected approach in the development of the aforementioned competencies. Once the analysis of the information collected was done, it was found that the personal interaction of the students in the classroom promotes and facilitates the use of English and the effective development of the activities designed for the application of the approach, in addition to the development of activities of Oral production, which are the basis of the communicative approach, have a positive impact on student motivation and on the development of oral competence, at the levels of comprehension and production.
Keywords: Communicative approach; oral production; linguistics; motivation.